“Longa peregrinação no novo mundo”: a congregação das filhas da caridade e a trajetória missionária de Irmã Pascal na América do Sul (1881-1882) - SANTOS, Camila Gonçalves (2024)
This work analyzes the missionary trajectory of Sister Pascal, a missionary of the Congregation of the Daughters of Charity of Saint Vincent de Paul, who traveled through South America between 1881 and 1882. Leaving France to visit some Vincentian houses on the continent, Sister Pascal recorded her entire itinerary in a travel report and periodically sent letters to the Mother House in Paris. The missionary was in Brazil, Uruguay, Argentina, Paraguay, Chile and Peru, constantly moving around within these countries in order to assess the state of the works of the congregation to which she belonged. During this time, she also experienced cultural contacts with different societies, moving around different geographies and adapting to the places she traveled. Based on the theoretical-methodological contribution of Connected History, this research seeks to understand, from her writings, the dynamics of congregational functioning in the spaces she visited, during a period when the congregation was well established in South America, and analyzes how cultural contacts were experienced by Sister Pascal during her journey.